2022
DOI: 10.5365/wpsar.2022.13.2.902
|View full text |Cite
|
Sign up to set email alerts
|

Conducting verbal autopsy by telephone interview during the pandemic to support mortality surveillance: a feasibility study in Malaysia

Abstract: Objective: Verbal autopsy (VA) through face-to-face interviews with caregivers is a way to determine cause of death without medical certification. In Malaysia, the use of VA has improved mortality statistics. However, during the coronavirus disease 2019 (COVID-19) pandemic, face-to-face interviews were delayed, reducing VA data collection and affecting data for mortality surveillance. This study aims to investigate the feasibility and acceptability of conducting VA interviews via telephone calls, and the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Nevertheless, numerous studies have found that telephone interviews are as effective as face-to-face interviews [ 78 , 79 ]. According to one study, the results of VA interviews via phone calls were consistent with previous literature, which found that the telephone interview method to be feasible, accepted by caregivers and healthcare workers, and has a reliable level of data quality [ 80 ]. One potential issue with VA interviews is the risk of selection bias.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, numerous studies have found that telephone interviews are as effective as face-to-face interviews [ 78 , 79 ]. According to one study, the results of VA interviews via phone calls were consistent with previous literature, which found that the telephone interview method to be feasible, accepted by caregivers and healthcare workers, and has a reliable level of data quality [ 80 ]. One potential issue with VA interviews is the risk of selection bias.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, numerous studies have found that telephone interviews are as effective as faceto-face interviews [71,72]. According to one study, the results of VA interviews via phone calls were consistent with previous literature, which found that the telephone interview method to be feasible, accepted by caregivers and healthcare workers, and has a reliable level of data quality [73]. Given the ethical nature of VA, it can arguably be said that conducting distant VA interviews on a fairly small sample in an area where VA has never been practiced before can be viewed as a strength in this study from an ethical perspective, which has the potential of reducing unwanted emotional or cultural consequences.…”
Section: Discussionsupporting
confidence: 75%
“…All the studies included in our systematic review with data on deaths reported were from the Sierra Leone hotline. Out of Africa, researchers in Malaysia showed that it was feasible to use mobile phones to support mortality surveillance during the COVID-19 pandemic where face-to-face contacts were severely restricted [ 43 ]. Also, in non-outbreak settings, some studies have shown the usefulness of mobile telephones.…”
Section: Discussionmentioning
confidence: 99%